2018
DOI: 10.1177/0192623318809000
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Features of Corneal Phospholipidosis in Juvenile White Rabbits Induced by Ocular Instillation of Chloroquine or Amiodarone

Abstract: Cationic amphiphilic drugs (CADs) can induce phospholipidosis (PLD) in organs/tissues. Several ophthalmic pharmaceuticals containing CADs are marketed and used in children. To investigate the effect of PLD on the developing cornea, chloroquine and amiodarone, which are representative CADs, were applied topically to the eyes of juvenile rabbits, and the effects in juvenile rabbits were compared with those in young adult rabbits. Diffuse corneal cloudiness was observed in chloroquine-and amiodarone-treated eyes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…33,34 There are several reports of juvenile rabbits being used for toxicological evaluations for topical ocular drugs or intravitreal injection agents. [4][5][6]35 When conducting juvenile toxicity studies, it is important to distinguish the changes due to test agent administration from the normal histology of immature organs/tissues. In ocular instillation studies, the eye should be focused on the toxicological evaluation since it is directly exposed to the test articles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33,34 There are several reports of juvenile rabbits being used for toxicological evaluations for topical ocular drugs or intravitreal injection agents. [4][5][6]35 When conducting juvenile toxicity studies, it is important to distinguish the changes due to test agent administration from the normal histology of immature organs/tissues. In ocular instillation studies, the eye should be focused on the toxicological evaluation since it is directly exposed to the test articles.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the safety of drug administration on immature ocular tissues has been performed in several studies using juvenile rabbits. These have included juvenile rabbit toxicity studies examining the effects of topical ocular instillation of chloroquine or amiodarone, 4 or the intravitreal administration of bevacizumab. 5,6 A knowledge of comparative postnatal morphological characteristics is important to inform the choice of the age of animals used in juvenile toxicity studies for the assessment of risk in pediatrics.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies with rabbits fed high-cholesterol diets have also demonstrated light and transmission electron microscopic effects in other regions of the globe including: lipid-laden macrophages in the choroid and suprachoroid; lipid accumulation in the retinal pigment epithelium (RPE) and astrocytes; Bruch’s membrane thickening; RPE hypertrophy; Müller cell and astrocyte activation; and degeneration and/or necrosis of choroidal vessel endothelium and retinal neurons 274 , 275 , 276 , 277 . Instillation of cationic amphiphilic drugs in juvenile white rabbits induce corneal phospholipidosis 278 .…”
Section: Section 16: Special Sensesmentioning
confidence: 99%
“…There are some clinical and experimental reports suggested that CLQ treatment causes ocular toxicity including keratopathy, ciliary body involvement, lens opacities, and retinopathy and retinopathy is the major concern (Yam & Kwok, 2006;Yamagiwa et al, 2019). On the contrary, other studies have suggested that low doses of CLQ administrations protect retinal ganglion cells by attenuating ROS levels and modulating apoptosis induced by glutamate (Ma et al).…”
Section: Discussionmentioning
confidence: 99%